Addressing Anti-Black Racism through the Social Work Curriculum: Informed, Prepared and Competent?. Issue 2 (27th May 2022) - Moore, Sharon E.; Sterrett-Hong, Emma M.; Miller, Shawnise Martin; Foreman, Jennifer; Boamah, Daniel A.; Storer, Heather; Nwachuku, Brittany; Adams, Monica M.; Moon, Heehyul; Jackson-Hurley, Carmellia; Frierson, Kimberly; Doub, DeShara C.
ABSTRACT: Racism is a pervasive system that permeates all social activity within U.S. society and for over four hundred years has constantly reproduced systems of inequality and disparate outcomes for Black people. Increasingly, attention has been given to integrating anti-racist content and methods into social work education and practice. By integrating concepts from racial equity and liberatory education theories, and providing a case example of one university's process of critically assessing students' experiences of how anti-racist pedagogies manifest within social work's implicit and explicit curriculum, this paper offers insights into potential strategies to prepare social work students to adequately address the needs of Black clients upon graduation.